PELATIHAN PEMBUATAN SOAL HOT BAGI GURU SEKOLAH MENENGAH ATAS DI SMA ISLAM ULIIL ALBAAB NW LENDANG JARAN - Qomaruddin (LPP ARROSYIDIN, 2024)
Higher Order Thinking (HOT) based questions are designed to measure students' abilities in critical, analytical and creative thinking. This type of problem requires students' ability to apply their knowledge in solving complex problems, going beyond simply memorizing specific facts. Through effective implementation and assessment of HOT-based questions, educators can provide opportunities for students to improve their problem-solving abilities, creativity and independent learning. Although the use of HOT-based questions offers various benefits, challenges such as question formulation, student readiness, objective assessment, and resource limitations also need to be overcome. Overcoming these challenges requires dedication, training, and continuous improvement in designing and evaluating HOT-based questions. Overall, HOT-based questions are a valuable tool in measuring students' cognitive abilities and developing critical thinking skills. By integrating these questions into the educational curriculum, educators can create a more engaging and intellectually stimulating learning environment that helps students hone their analytical and creative thinking skills. Implementing HOT-based questions requires a strategic approach and ongoing support to maximize its effectiveness in preparing students for success in the world of academics and real life.